2014
DOI: 10.1098/rstb.2013.0598
|View full text |Cite
|
Sign up to set email alerts
|

Probing astroglia with carbon nanotubes: modulation of form and function

Abstract: 0000-0003-2592-9898; VP, 0000-0002-4643-2197 Carbon nanotubes (CNTs) have shown much promise in neurobiology and biomedicine. Their structural stability and ease of chemical modification make them compatible for biological applications. In this review, we discuss the effects that chemically functionalized CNTs, applied as colloidal solutes or used as strata, have on the morpho-functional properties of astrocytes, the most abundant cells present in the brain, with an insight into the potential use of CNTs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…It has been shown that functionalized single-walled carbon nanotube films induce morphological and functional changes such as increased glutamate uptake in mouse cortical astrocytes 28 29 67 . Moreover, it has been recently discovered that nano-roughness of silica films can modulate the function of hippocampal neurons and their relationship with astrocytes via mechanical stimuli 31 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that functionalized single-walled carbon nanotube films induce morphological and functional changes such as increased glutamate uptake in mouse cortical astrocytes 28 29 67 . Moreover, it has been recently discovered that nano-roughness of silica films can modulate the function of hippocampal neurons and their relationship with astrocytes via mechanical stimuli 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Single-walled carbon nanotubes (SWCNTs) have been considered candidates for applications in biotechnology and biomedicine [ 1 , 2 ], and in particular for neural applications [ 3 , 4 ]. When chemically functionalized with polyethylene glycol (PEG), SWCNTs render water solubility [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our present work logically sprouts from our previous studies of the effect that SWCNTs have on primary astrocytes, as reviewed elsewhere [15]. Briefly, to investigate the effects of SWCNTs on primary mouse astrocytes in culture, we used graft copolymers/conjugates of SWCNTs chemically functionalized with polyethylene glycol (PEG) or poly-m-aminobenzene sulfonic acid (PABS) making SWCNTs water soluble (wsSWCNTs) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…When added to the culturing medium, wsSWCNTs were able to make astrocytes larger and less round compared to the untreated astrocytes, but these nanomaterials did not affect astrocyte vitality, that is, cell adhesion, proliferation and death rate [17]. Generally, the data indicated the necessity of the SWCNT backbone for the changes induced by the water-soluble graft copolymers, while some subtle differences in the effects that SWCNTs had on astrocytes (for clarity details omitted here, but summarized and reviewed in [15] and Table 1 of [17]; also see discussion) were due to the various functional groups attached to the SWCNTs.…”
Section: Introductionmentioning
confidence: 99%